Establishment and application of an intelligent management platform for home medication for children with leukemia - Dahui Zhong; Yang Liu; Lin Mo; Li Zhang; Xuelan Shen; Qiumeng Xiang (PLoS ONE, 2025)
Objective This study aimed to establish an intelligent management platform for home medication for children with leukemia and verify its efficacy in enhancing home medication compliance in children with leukemia using intelligent approaches. Method Children with leukemia who were treated in a hospital in Chongqing, China, between January and April 2022 were enrolled. The user intentions and requirements for an intelligent management platform for home medication were analyzed for both the patient and their family, leading to the establishment of an intelligent management platform with multiple ports. Children with leukemia who were at the maintenance stage of the treatment during July-December 2023, were randomly divided into control and experimental groups. For medication management, hard copies of chemotherapy records and regular outpatient follow-up data were collected from both groups. For the experimental group, data were also acquired from the intelligent management platform. The self-efficacy in rational medication, rate of missed/incorrect administration, and unplanned admission rate of the two groups were assessed after three months of intervention. The usage efficiency of the platform was also evaluated in children and caregivers in the experimental group. Results The intelligent management platform for home medication for children with leukemia comprised a patient-end WeChat applet, a medical staff-end WeChat applet, and a Web management end, with each applet having distinct functions. After three months of intervention, the self-efficacy score in rational medication of the experimental group was significantly higher than that of the control group (33.93 vs. 30.03, P <  0.05). Furthermore, the rate of missed or incorrect administration of the experimental group was significantly lower than that of the control group (10% vs. 26.76%, P <  0.05). The rates of unplanned admission of the two groups did not differ significantly (P >  0.05). Moreover, the overall satisfaction of the experimental group of children and caregivers with the proposed platform was 94.29%. Conclusion The proposed management platform for home medication for children with leukemia was associated with increased self-efficacy in the rational medication of these children and a reduced missed/incorrect administration rate, thereby providing an effective approach for more accurate and safer home medication for these children.